Foot placement of the equine forelimb: Relationship between foot conformation, foot placement and movement asymmetry. (18th December 2014) - Wilson, A.; Agass, R.; Vaux, S.; Sherlock, E.; Day, P.; Pfau, T.; Weller, R.
Summary: Reasons for performing study: Hoof conformation, foot placement and movement asymmetry are routinely assessed as part of the lameness examination. However, to date, few studies have described these parameters, or the interplay between them, in the general horse population. Objectives: To assess foot conformation and foot placement in the forelimbs of a group of general purpose horses and investigate the relationships between foot placement, foot conformation and movement asymmetry. Study design: Observational cross‐sectional study. Methods: Forty‐three horses were included in the study. Measurements were taken from photographs of each forelimb to assess foot conformation. Video footage was recorded simultaneously from perpendicular cameras at both walk and trot and used to categorise foot placement. Inertial sensor data were used to assess head movement asymmetry in trot. Results: There was a high degree of variation in foot placement between and within horses, but a 'lateral heel' placement was most common in walk and a 'lateral' placement most common in trot. Foot placement was associated with dorsal and palmar hoof angles but there was no relationship between foot placement and the other conformation parameters, nor with movement asymmetry. Moderate negative correlations were found between several of the conformation parameters and movement asymmetry. Conclusions: A relationship exists between foot conformation and movement asymmetry with decreasing hoof width and hoof length related to increasing amount of movement asymmetry. In the population of horses studied here – deemed to be 'well functioning' by their owners/riders – foot placement was found to be independent of movement asymmetry and, to a large extent, independent of foot conformation.